Opportunities for reproductive tourism: cost and quality advantages of Turkey in the provision of in-vitro Fertilization (IVF) services - M. Said Yildiz; M. Mahmud Khan (BMC, 2016)
Abstract Background The scale and scope of medical tourism have expanded rapidly over the last few decades. Turkey is becoming an important player in this market because of its relatively better service quality and large comparative cost advantage. Methods This paper compares cost, quality and effectiveness of in-vitro fertilization (IVF) in the USA and in Turkey. The data from Turkey were obtained from a hospital specializing in IVF services and the US data came from secondary sources. Package price offered by the dominant IVF-service provider to international patients in Turkey was used as a measure of cost for Turkey while IVF-specific service prices were used to estimate the cost for USA. To compare quality and effectiveness of IVF services, a number of general clinical quality indicators and IVF success rate were used. Results Indicators of quality, cost and success rate in the Turkish hospital were found to be better than the corresponding indicators in US hospitals. The cost difference of IVF services between USA and Turkey is so significant that the overall cost of obtaining the service from Turkey remains lower even with additional expenses for travel and accommodation. Conclusions Cost-effectiveness ratio of IVF treatment per successful clinical pregnancy was much lower in Turkey than in the USA. It appears that cost and quality are the two most important factors affecting demand for health care services by international patients in Turkey. Like other important players in the medical tourism market, Turkey should be able to take advantage of its success in IVF, a highly specialized niche market, to transform its health system into an important exporter of general health services.